An Analysis of Parenting Style which are Reflected in Movie “Run” by Aneesh Chaganty - Rosa, Selvia; Priyoto, Priyoto; Mujani, Sahril (STIBA IEC JAKARTA, 2024)
The aim of this study is to understand deeper about how psychology affects directly to parenting styles especially in a mother figure, thus eventually affect children's behaviors in their social stand towards themselves and people around them, as well as the kind of manners and actions they take when they are faced with problems. The researcher used qualitative method to collect data based on the research problem. Journals, websites, previous researches and other articles were used as data sources to analyze this film. In conclusion, Diane teaches us that loving means trusting and supporting each other with care, giving without expecting something in return, and that loving to family is always on greatest importance. She states how she always believes in Chloe’s capabilities regardless how fragile Chloe seems to be with her countless diseases. She proves how care she does and how supportive she is to her daughter. But in the end of the day, all those sacrifices and considerably amount of love and care she gives to Chloe, her impulsive lies ruin everything she built for 17 years and gone in an instant. Ultimately, giving the loved ones freedom for their life choice and keeping honesty lives in between are the best thing someone could do to support them. The purpose of this study is to focus on the parenting styles of single mothers towards her daughter with disabilities. The researcher applies the theory from Diana Baumrind (1971) about parenting styles.